2003
DOI: 10.1016/s0304-3835(03)00385-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Fhit, Mlh1, and P53 protein in human gallbladder carcinoma

Abstract: There is limited information on the molecular changes involved in the pathogenesis of gallbladder carcinoma (GBC). The Fragile Histidine Triad (FHIT) gene, encompassing the FRA3B fragile site at chromosome 3p14.2, is a candidate tumor suppressor gene in a variety of human malignancies. Recent studies have suggested that Fhit inactivation can be a consequence of defects in mismatch repair proteins. We analyzed Fhit and Mlh1 protein expressions using immunohistochemical methods in 20 GBCs and three gallbladder a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 28 publications
1
20
0
1
Order By: Relevance
“…Replacement of the FHIT gene, using recombinant adenoviral and adenoassociated viral FHIT vectors resulted in apoptosis via the caspase pathway in pancreatic cancer cell lines, in accord with a role for Fhit in pancreatic cancer initiation 26. The role of Fhit or Wwox in other biliary tumors has not been explored extensively, though there are two reports of Fhit locus silencing by methylation in gallbladder cancers 27,28. Herein, we have shown that Fhit and Wwox proteins are lost in cancers arising from the pancreas, ampulla of Vater, and gallbladder, independent of other well known genetic alterations.…”
Section: Discussionmentioning
confidence: 74%
“…Replacement of the FHIT gene, using recombinant adenoviral and adenoassociated viral FHIT vectors resulted in apoptosis via the caspase pathway in pancreatic cancer cell lines, in accord with a role for Fhit in pancreatic cancer initiation 26. The role of Fhit or Wwox in other biliary tumors has not been explored extensively, though there are two reports of Fhit locus silencing by methylation in gallbladder cancers 27,28. Herein, we have shown that Fhit and Wwox proteins are lost in cancers arising from the pancreas, ampulla of Vater, and gallbladder, independent of other well known genetic alterations.…”
Section: Discussionmentioning
confidence: 74%
“…10,39 As far as we know, there is no report concerning methylation of the FHIT gene in gallbladder cancers; nevertheless, immunohistochemical expression of FHIT has been described as considerably reduced or absent in 45% to 79% of gallbladder carcinomas and in 38% to 55% of areas of adjacent dysplasia. 40,41 Loss of immunohistochemical expression of FHIT has also been associated with a reduction in MLH1 expression, and its changes appear early in gallbladder tumorigenesis. 41 In our series, the AIP for FHIT was 21%, compared to the 30% methylation in the gene promoter area, showing no relationship to the morphological parameters nor to any of the other genes in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Koda et al 34 analyzed Fhit and Mlh1 protein expressions by the immunohistochemical method in gallbladder cancers, and reported that reduced Fhit expression was significantly associated with an absence of Mlh1 protein expression in gallbladder cancers. Wistuba et al 35 also investigated Fhit expression by the immunohistochemical method during the multistage sequential development of gallbladder carcinoma, including dysplastic epithelia.…”
Section: Gallbladder Cancermentioning
confidence: 99%